A New Hybrid of Conjugate Gradient Method with Descent Properties - Shoid, Syazni; Zull, Norhaslinda; Rivaie, Mohd; Mamat, Mustafa; Liza Ghazali, Puspa; Afendee Mohamed, Mohamad (International Journal of Engineering and Technology, 2018)
Many researchers are interested in developing and improving the conjugate gradient (CG) method because of its convergence properties and efficiency in solving large-scale problems. This work introduces new CG coefficient ( ) will be presented in such a way to improve the performance of the previous CG methods. The new method is the hybrid between HS and SYRM methods. This method always produces a descent search direction at each iteration. The preliminary numerical comparisons with some others CG methods have shown that this new method is efficient in solving all given problems under Strong Wolfe Powell (SWP) line search condition.Â Â